The contradictory politics of the right to travel: mobilities, borders & tourism - Bianchi, R. V.; Stephenson, M. L. *; Hannam, K. (Routledge, 2020)
The freedom of movement and right to travel are intrinsic to the growth of international tourism. Notwithstanding the inchoate nature of the right to tourism, the entitlement to travel and to pursue tourism without hindrance is firmly established in advanced capitalist societies. Moreover, the right to tourism has been recently enshrined in the 2017 United Nations World Tourism Organisation (UNWTO) Framework Convention on Tourism Ethics. Tourists’ ease of mobility contrasts starkly with the movements of less privileged forms of mobility that may be variously constrained by racism, xenophobia and restrictive border controls. This paper contends that rather than a mere reflection of accumulated political rights (citizenship), such unequal and differentiated mobilities are conditioned by a complex assemblage of discursive frameworks and structural forces that are played out in specific historical-geographic contexts. Accordingly, we argue that the rights associated with global tourism must be analysed in the context of the contradictory politics of global mobility, or indeed in terms of the ‘mobility crisis’. This ‘crisis’ is one that is rooted in and shaped by the cumulative legacy of past colonial orders, global capitalism and geopolitical realignments, in addition to multi-scalar systems of governance through which borders are constituted, managed and policed.